THE EFFECTIVENESS OF THE MARRIAGE MANAGEMENT INFORMATION SYSTEM (SIMKAH) IN IMPROVING THE QUALITY OF MARRIAGE ADMINISTRATION SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA) OF CANDI SUB-DISTRICT - Zahraamadhani, Salsabila Az; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to evaluate the effectiveness of the implementation of the Marriage Management Information System (SIMKAH) in improving the quality of marriage administrative services at the Office of Religious Affairs (KUA) in Candi District. Method: A descriptive qualitative approach was employed, utilizing data collection techniques such as in-depth interviews, direct observation, and document analysis, and data were analyzed using the interactive model of Miles and Huberman, with triangulation applied to ensure data validity. Result: The findings reveal that SIMKAH enhances service responsiveness by improving time efficiency and digital access, reinforces transparency through the disclosure of costs and procedures, and strengthens internal accountability via auditable digital records, however, the implementation still faces several challenges, including limited infrastructure, low digital literacy among the community, and suboptimal functionality of interactive features such as data revision and complaint tracking. Novelty: These findings suggest that SIMKAH holds significant potential as a form of digital transformation in public services, nevertheless, further development is needed to ensure greater inclusiveness and public participation, and this study contributes to the formulation of digital policy improvements in marriage service administration, particularly at the sub-district level.